Golden Temple of Jehol, by night (Max Rigot Selling Co)
Replica of the celebrated Chinese Lama Temple, is the gift to the Exposition of Vincent Bendix. The Golden Pavilion, seat of worship of the Manchu emperors, was copied faithfully by North Chinese architects and artisans, shipped in 28,000 pieces to Chicago and put together like the parts of some huge Chinese puzzle.